Legal personality and the institute of death in Roman law (Revista do Tribunal Regional Federal da 3ª Região, 2019)
The construction of knowledge about legal personality depends on an analysis a priori of the understanding like a man or a subject of rights for the Roman legal order. Although this issue involves controversial points, such as birth with extrauterine life and human form, the objective is to establish what are the main attributes the individual must gather in order to get rights and contract obligations, under the application of the corpus juris civilis norms. Subsequently, it will be verified that the legal personality has its own formative requirements, reflecting on the performance of man in practically all sectors of society, mostly in the practice of legal acts and businesses, the exercise of political rights, and even in the position in the family nucleus. Finally, the institute of civil death is analyzed, especially since it is a peculiar way of extinction of the legal personality, without harming the life of the man.
Keywords: Roman Law; legal personality; civil death